Scabies Evaluated by Dermoscopy and Fluorescence Microscopy: A Case Report - Li-Wen Zhang; Wen-Ju Wang; Xue-Ying Liu; Lei Xu; Lu Zheng; Cong-Hui Li; Yong-Hong Lu (International Journal of Dermatology and Venerology, 2021)
Abstract. Introduction:. Scabies is an infectious skin disorder caused by the mite Sarcoptes scabiei. The diagnosis of scabies is often confirmed by microscopic detection of scabies mites, eggs, or feces. We herein describe the diagnosis of scabies in a boy with the assistance of dermoscopy and fluorescence microscopy. Case presentation:. A 16-year-old Chinese boy presented with a 2-month history of extensive papules and excoriations with intense pruritus on the trunk and limbs. Dermoscopy showed a sinuous burrow in the finger webs with a brown jet-shaped triangular structure at the end. A fluorescence microscopy revealed a hatching egg and a mite. The boy was diagnosed with scabies and treated with 5% sulfur ointment. Discussion:. The use of dermoscopy in patients with scabies reveals a sinuous burrow with a brown jet-shaped triangular structure composed of the pigmented head and anterior legs of the mite[1]. A fluorescence microscopy revealed mites and eggs with blue fluorescence after staining, allowing us to easily identify scabies. Conlcusion:. The combination of dermoscopy-guided tape testing with fluorescence staining technology may enhance the diagnostic accuracy and efficiency of scabies.